2023
DOI: 10.1007/s10753-023-01846-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Myeloperoxidase in ROS Generation and Inflammation Response on Prostate Epithelial Cells

Abstract: Myeloperoxidase (MPO) has been reported in prostate tissue, and considering its pro-oxidant properties, this location might be linked to prostate pathology. The possibility that the glandular prostatic tissue might be the source of MPO and its potential inflammatory effects must be tested. Human prostate material was obtained from prostate biopsies and radical prostatectomies. Immunohistochemistry was performed using MPO-specific human antibody. In situ hybridization using MPO-specific probes and laser-assiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Myeloperoxidase (MPO) is a functional marker and activation marker of neutrophils, and its level and activity represent the function and activity of polymorphonuclear neutrophils (PMN). A large number of studies have shown that MPO can be used as a marker to indicate the inflammatory infiltration of tissues ( Roumeguère et al, 2023 ). As shown in Figure 9A , at both time points, the Rg1-Gel group observed the fewest inflammatory cells (MPO-positive, MPO + ) in the tissue surrounding the wound, and the percentage of MPO-positive cells is shown in Figure 9B .…”
Section: Resultsmentioning
confidence: 99%
“…Myeloperoxidase (MPO) is a functional marker and activation marker of neutrophils, and its level and activity represent the function and activity of polymorphonuclear neutrophils (PMN). A large number of studies have shown that MPO can be used as a marker to indicate the inflammatory infiltration of tissues ( Roumeguère et al, 2023 ). As shown in Figure 9A , at both time points, the Rg1-Gel group observed the fewest inflammatory cells (MPO-positive, MPO + ) in the tissue surrounding the wound, and the percentage of MPO-positive cells is shown in Figure 9B .…”
Section: Resultsmentioning
confidence: 99%